Blacks against Brown : the intra-racial struggle over segregated schools in Topeka, Kansas - Cheney, Charise L.; Project Muse. (Chapel Hill : The University of North Carolina Press, 2024)
"Brown v. Board of Education of Topeka, Kansas (1954) is regarded as one of the most significant civil rights moments in American history. Historical observers have widely viewed this landmark Supreme Court decision as a significant sign of racial progress for African Americans. However, there is another historical perspective that tells a much more complex tale of Black resistance to the NAACP's decision to pursue desegregating America's public schools. This multifaceted history documents the intra-racial conflict among Black Topekans over the city's segregated schools. Black resistance to school integration challenges conventional narratives about Brown by highlighting community concerns about economic and educational opportunities for Black educators and students and Black residents' pride in all-Black schools. This history of the local story behind Brown v. Board contributes to a literature that provides a fuller and more complex perspective on African Americans and their relationship to Black education and segregated schools during the Jim Crow era"--
Over John Brown's dead body: white supremacy and white liberalism in Kansas -- The alchemy of race and rights: separate but equal in Topeka Public Schools, 1861-1954 -- Reading, ri(gh)ting, and resistance: racial uplift ideologies and practices in Topeka's all-Black schools, 1929-1954 -- Graham v. Board and the clash of the Black counterpublics -- Harrison Caldwell: the unsung Black antihero of Brown -- Blacks against Brown: the final chapter, 1941-1954.
Includes bibliographical references and index.
Charise L. Cheney is professor of Indigenous, race, and ethnic studies at the University of Oregon.
Print version record.
JSTOR
Keywords: Brown, Oliver, -- 1918-1961 -- Trials, litigation, etc; Topeka (Kan.). -- Board of Education -- Trials, litigation, etc; African Americans -- Kansas -- Topeka -- Social conditions -- 20th century; African American schools -- Kansas -- Topeka -- History -- 20th century; School integration -- Law and legislation -- Kansas -- Topeka -- History -- 20th century; Discrimination in education -- Law and legislation -- Kansas -- Topeka -- History -- 20th century; Educational equalization -- Law and legislation -- Kansas -- Topeka -- History -- 20th century; Segregation in education -- Law and legislation -- Kansas -- Topeka -- History -- 20th century; Topeka (Kan.) -- Race relations; Noirs américains -- Kansas -- Topeka -- Conditions sociales -- 20e siècle.; Écoles noires américaines -- Kansas -- Topeka -- Histoire -- 20e siècle.; SOCIAL SCIENCE / Race & Ethnic Relations; SOCIAL SCIENCE / Ethnic Studies / American / African American & Black Studies